Influence of Milling Energy and Precursors on CaKFe4As4 Polycrystalline Superconductor Morphology - Anastasiya Duchenko; Achille Angrisani Armenio; Giuseppe Celentano; Alessandra Fava; Daniele Mirabile Gattia; Nicola Pompeo; Enrico Silva; Francesca Varsano; Andrea Masi (Crystals)
The synthesis of CaKFe4As4 superconducting compounds either requires the adoption of high-temperature synthesis or implies the intimate mixing of the precursors via mechanochemical routes before the thermal step in order to avoid chemical inhomogeneities that lead to thermodynamically stable unwanted phases. High Energy Ball Milling (HEBM) represents a useful tool to ensure the comminution of the elements and their dispersion to obtain the target phase. The adoption of mechanochemical treatments is, however, known to lead to the formation of aggregates of small crystals, leading to a powder morphology not optimal for practical applications. In this work, we report our findings in the synthesis of CaKFe4As4 polycrystalline compounds showing the effect of milling energy on the morphology and phase composition of the powders. To overcome the limits of conventional synthesis, we report the results of a novel synthesis approach for CaKFe4As4 materials, highlighting how the choice of the proper precursors and the adoption of milder treatments can represent the key to optimizing the powder morphology.